Nexus between constructs of social cognitive theory model and diabetes self-management among Ghanaian diabetic patients: A mediation modelling approach. - Yaa Obirikorang; Emmanuel Acheampong; Enoch Odame Anto; Ebenezer Afrifa-Yamoah; Eric Adua; John Taylor; Linda Ahenkorah Fondjo; Sylvester Yao Lokpo; Evans Asamoah Adu; Bernard Adutwum; Enoch Ofori Antwi; Emmanuella Nsenbah Acheampong; et al. (Public Library of Science (PLoS), 2022)
The promotion of Diabetes Self-Management (DSM) practices, education, and support is vital to improving the care and wellbeing of diabetic patients. Identifying factors that affect DSM behaviours may be useful to promote healthy living among these patients. The study assessed the determinants of DSM practices among Type 2 diabetes mellitus (T2DM) patients using a model-based social cognitive theory (SCT). This cross-sectional study comprised 420 (T2DM) patients who visited the Diabetic Clinic of the Komfo Anokye Teaching Hospital (KATH), Kumasi-Ghana. Data was collected using self-structured questionnaires to obtain socio-demographic characteristics, T2DM-related knowledge, DSM practices, SCT constructs; beliefs in treatment effectiveness, level of self-efficacy, perceived family support, and healthcare provider-patient communication. Path analysis was used to determine direct and indirect effects of T2DM-related knowledge, perceived family support, and healthcare provider service on DSM practices with level of self-efficacy mediating the relationships, and beliefs in treatment effectiveness as moderators. The mean age of the participants was 53.1(SD = 11.4) years and the average disease duration of T2DM was 10 years. Most of the participants (65.5%) had high (>6.1mmol/L) fasting blood glucose (FBG) with an average of 6.93(SD = 2.41). The path analysis model revealed that age (p = 0.176), gender (p = 0.901), and duration of T2DM (p = 0.119) did not confound the relationships between the SCT constructs and DSM specified in the model. A significant direct positive effect of family and friends' support (Critical ratio (CR) = 5.279, p < 0.001) on DSM was observed. Self-efficacy was a significant mediator in this relationship (CR = 4.833, p < 0.001). There were significant conditional indirect effects (CIE) for knowledge of T2DM and family and friends' support at medium and high levels of belief in treatment effectiveness (p < 0.05) via level of self-efficacy on DSM practices. However, no evidence of moderated-mediation was observed for the exogenous variables on DSM. Diabetes-related knowledge of T2DM, family and friends' support, level of self-efficacy, and belief in treatment effectiveness are crucial in DSM practices among Ghanaian T2DM patients. It is incumbent to consider these factors when designing interventions to improve DSM adherence.